Strengthening School‐Based Support Systems for Children and Youth With Developmental Coordination Disorder: A National Survey of Canadian Parents - Erin S. Klein; Nicole Pereira; Arman Gill; Jill G. Zwicker (Child: Care, Health and Development, 2026)
ABSTRACT Background Parents of children with Developmental Coordination Disorder (DCD) face barriers in accessing school‐based services and supports for their children despite challenges in academic attainment related to motor coordination difficulties and secondary consequences associated with DCD. Changes to service delivery are vital for student success but need to be rooted in parent‐ and child‐identified needs and priorities. Purpose To explore parent perspectives of children (5–18 years) with DCD on the barriers and facilitators in accessing clinical and curriculum‐based services and supports across Canada. Method We circulated an online cross‐sectional survey using a multi‐pronged recruitment strategy to parents of children with suspected or confirmed DCD across Canada from November 2021 to June 2022. Quantitative data were analysed using descriptive statistics and chi‐square tests. Exploratory content analysis was completed for qualitative data. Findings Parents across Canada responded, with 488 included surveys. There is inconsistent availability and access to school‐based therapies, creating an inequitable service delivery. There are long waitlists, limited frequency of visits and often children are ineligible for services. Despite classroom accommodations and resource support, parents report a lack of educator awareness and understanding with variable adherence to needed curriculum adaptations. Canadian school supports and services are failing to meet the needs of children with DCD, resulting in negative trajectories in physical, social, emotional and academic pursuits. Conclusion Transformative changes are required for provision of school‐based clinical and curriculum services and supports. Evidence‐informed approaches, such as a tiered service delivery model, can provide effective and financially viable processes, ensuring positive outcomes for students with DCD.